EFL students’ reading comprehension problems: Linguistic and non-linguistic complexities - Usman Kasim; Siti Raisha (Universitas Syiah Kuala, 2017)
The goal of this study was to investigate how to overcome reading comprehension problems amongst students in an EFL classroom. Specifically, this study tries to identify both linguistic and non-linguistic reading comprehension problems. Further, the study focused on fifty of the fifth-semester students from the English department in the Teaching Faculty at Syiah Kuala University. Data collection was conducted by distributing the English Reading Comprehension Problems Questionnaire modified from Al Seyabi and Tuzlukova (2015). The data was analyzed by using quantitative analysis to get the mean scores and percentages. The results indicated that the students experienced the most reading problems in the areas of linguistics (69%). In addition, based on mean scores and percentages from the questionnaire, the results shown that the biggest reading comprehension problem was with semantics in which 81% of the participants considered unfamiliar vocabulary was their major problem in comprehending English texts.